2004
DOI: 10.1155/s0161171204312445
|View full text |Cite
|
Sign up to set email alerts
|

The 3D Happel model for complete isotropic Stokes flow

Abstract: The creeping flow through a swarm of spherical particles that move with constant velocity in an arbitrary direction and rotate with an arbitrary constant angular velocity in a quiescent Newtonian fluid is analyzed with a 3D sphere-in-cell model. The mathematical treatment is based on the two-concentric-spheres model. The inner sphere comprises one of the particles in the swarm and the outer sphere consists of a fluid envelope. The appropriate boundary conditions of this non-axisymmetric formulation are similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Dassios et al [21] demonstrated how Papkovich-Neuber representations of the flow fields were correlated to the general solution of Stokes equations in spheroidal geometry. Furthermore, Dassios and Vafeas [22] corroborated the powerfulness and usability of the above 3D Papkovich-Neuber representation by obtaining a closed-form solution for a Happel-type 3D Stokes flow through a swarm of translating and rotating spherical particles.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Dassios et al [21] demonstrated how Papkovich-Neuber representations of the flow fields were correlated to the general solution of Stokes equations in spheroidal geometry. Furthermore, Dassios and Vafeas [22] corroborated the powerfulness and usability of the above 3D Papkovich-Neuber representation by obtaining a closed-form solution for a Happel-type 3D Stokes flow through a swarm of translating and rotating spherical particles.…”
Section: Introductionmentioning
confidence: 70%
“…, n and q = e, o with p = int, ext, specifies the system's solution, achieved up to any precise level, where the targeted degree of accuracy is attained. Thereupon, the flow fields follow from Equations ( 19)-( 21) with (22), where the relationships of Equations ( 23)-( 25) are readily incorporated.…”
Section: Boundary Value Problem and Analytical Solutionmentioning
confidence: 99%
“…The computed q′′ was equal to −0.021 (C/m 2 ) in good agreement with the values reported in the literature. 39,40 In addition, q′′ and the equivalent diameter were used to calculate the protein surface potential obtaining −7.5 mV. Interestingly, the surface charges calculated by the Loẅdin method yielded a value of q′′ equal to −0.012 C/m 2 and a BSA surface potential equal to −4.9 mV 12 .…”
Section: Resultsmentioning
confidence: 99%
“…The fields are provided in a closed form fashion as full series expansions of ellipsoidal harmonic eigenfunctions. The velocity, to the first degree, which represents the leading term of the series, is sufficient for most engineering applications and also provides us with the corresponding full 3D solution for the sphere [10] after a proper reduction. The whole analysis is based on the Lamé functions and the theory of ellipsoidal harmonics.…”
Section: Particle-in-cell Models For Stokes Flow In Ellipsoidalmentioning
confidence: 99%